2010
DOI: 10.1523/jneurosci.0170-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol-Dependent Kinase Activity Regulates Transmitter Release from Cerebellar Synapses

Abstract: Changes in membrane cholesterol content can alter protein kinase activity, however, it is not known whether kinases regulating transmitter release are sensitive to membrane cholesterol content. Here we have used the cholesterol extracting agent methyl-␤-cyclodextrin to measure the effects of acute cholesterol reduction on transmitter release from cultured cerebellar neurons. Cholesterol depletion increased the frequency of spontaneous transmitter release without altering the amplitude and time course of mEPSCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 27 publications
3
25
0
Order By: Relevance
“…In order to avoid cholesterol depletion, the cells activate cholesterol synthesis in parallel with a down-regulation of the LXR target genes related to cholesterol efflux (ABCA1 and ApoE). Acute cholesterol depletion by cyclodextrin treatment results in altered membrane properties that can affect synaptic transmission in Purkinje cells and wildtype hippocampal neurons [57,58]. On the other hand, Sodero and coworkers have suggested that a sudden rise in excitatory neurotransmission activate CYP46A1-dependent mild cholesterol loss mechanisms to protect themselves from neuronal death [59].…”
Section: Discussionmentioning
confidence: 99%
“…In order to avoid cholesterol depletion, the cells activate cholesterol synthesis in parallel with a down-regulation of the LXR target genes related to cholesterol efflux (ABCA1 and ApoE). Acute cholesterol depletion by cyclodextrin treatment results in altered membrane properties that can affect synaptic transmission in Purkinje cells and wildtype hippocampal neurons [57,58]. On the other hand, Sodero and coworkers have suggested that a sudden rise in excitatory neurotransmission activate CYP46A1-dependent mild cholesterol loss mechanisms to protect themselves from neuronal death [59].…”
Section: Discussionmentioning
confidence: 99%
“…This has previously been used as a control to show cholesterolspecific effects of M␤CD (Suzuki et al, 2004;Smith et al, 2010). Sterol levels were increased in preparations incubated with this complex (Fig.…”
Section: Extraction Of Vesicular Sterols Prevents Recovery Of Synaptimentioning
confidence: 99%
“…In fact, it is being increasingly recognized that dysregulation of cholesterol metabolism and homeostasis may have a role in neurological diseases, such as Alzheimer's (Ledesma and Dotti, 2006;Gamba et al, 2012;Suzuki et al, 2013) and Huntington's (Valenza et al, 2005). On the other hand, cholesterol may influence multiple aspects of synaptic transmission (Pfrieger, 2003), both presynaptically, acting on neurotransmitter vesicle fusion (Deutsch and Kelly, 1981;Linetti et al, 2010;Smith et al, 2010;Mercer et al, 2012), and postsynaptically, altering neurotransmitter receptor diffusion (Renner et al, 2009) and endosomal dynamics (Hering et al, 2003;Hou et al, 2008). However, it remains to be established whether cholesterol metabolism is regulated by neuronal activity under physiological conditions, and particularly, what the molecular mechanisms are that link changes in cholesterol to the regulation of synaptic strength during plasticity.…”
Section: Ltp-triggered Cholesterol Redistribution Activates Cdc42 Andmentioning
confidence: 99%